Enola Holmes as a representation of equality in Enola Holmes (2020) movie - Desak Made Juli Ristiawati; I Wayan Juniartha (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2026)
This study examines the feminist characterization of the main character in Enola Holmes (2020) by applying Joseph M. Boggs’s theory of cinematic characterization alongside Kimberlé Crenshaw’s concept of intersectionality. The analysis concentrates on five selected scenes that illustrate Enola Holmes’s opposition to patriarchal expectations as expressed through dialogue, costume, physical actions, and visual symbolism. The findings indicate that Enola Holmes persistently subverts conventional gender roles by refusing marriage, satirizing male authority through caricature, engaging in physical combat while constrained by traditional feminine attire, and affirming her intellectual and professional abilities in the face of gender-based assumptions. Using Boggs’s framework, Enola Holmes’s internal qualities, outward behavior, and relationships are identified as key indicators of her feminist identity. From an intersectional perspective, the character’s age, gender, and social status intersect to intensify her marginalization; however, she actively negotiates these limitations with resilience and self-determination. Overall, the film offers a nuanced representation of young female empowerment within a patriarchal social structure, demonstrating that resistance may emerge through verbal, visual, physical, and symbolic forms. This study contributes to discussions on feminist representation in contemporary cinema and illustrates how cinematic techniques can effectively construct complex and intersectional female characters.